Pemahaman Guru Fisika tentang Implementasi Kurikulum 2013 (K-13) pada Pembelajaran Fisika Di MTs Darul Ulum - Effendi Effendi; Alimatu Fatmawati; Umi Kalsum (Pendidikan Fisika Universitas Nurul Huda, 2021)
This study aims to analyze the understanding of physics teachers at MTs Darul Ulum Karang Sari about K13 (2013 Curriculum), teacher readiness in learning, implementation of learning, and direction of learning development. The research on the understanding of physics teachers was carried out using a qualitative descriptive research method. The research subjects were four physics teachers at MTs Darul Ulum Karang Sari. Data was collected using interview and questionnaire techniques. The data were analyzed and classified by presenting the data, reducing the data, and making conclusions from the data. Based on the results of the study, it can be concluded that the physics teacher at MTs Darul Ulum has not fully understood the concept of the 2013 curriculum. Some teachers are more focused on character education contained in K-13. This understanding that focuses on character education has an impact on unclear learning objectives. The readiness of the physics teacher at MTs Darul Ulum to start learning is in accordance with the syllabus and lesson plans, although it is not optimal. For example, the teacher has prepared materials, methods, and media that will be used in learning. However, in the implementation, not all teachers do according to the 2013 curriculum. In the implementation in the classroom learning with the 2013 curriculum does not really show the difference with learning with KTSP. The assessment system has been done well by most teachers